Setia Sampai Terbukti: A Triadic Intervention in Persons With Leprosy to Improve Wellbeing and Reduce Stigma - Rufus Patty Wutun; R. Pasifikus Christa Wijaya (Universitas Nusa Cendana, 2019)
Persons with leprosy suffer physically, psychologically and socially. They feel punished, condemned, discarded and ostracized as the result of their stigma. We argued that leprosy management and complete healing better be done simultaneously on physiological, psychological, sociological and religious faith-spiritual levels, using triadic approach intervention. This study conducted in 2017 in Lembata District, Nusa Tenggara Timur, Indonesia. 42 leprosy cases were screened through laboratory examination conducted at Damian hospital. 28 leprosy patients agreed to receive the treatment in addition to leprosy medical treatment. 14 patients refused to participate. The Leprosy intervention model successfully enhances the improvements of 24 patients’ health. Spiritual/religious values can be used as a base of a positive view on leprosy management, empowering the family and community capacity on treating leprosy. Social integration is needed to improve the wellbeing of patients both physically and psychologically. This support helps patients to cope with negative feelings and reintegrating them into communities.